Probabilistic timing analysis of the h-BEB collision resolution algorithm - Ricardo Moraes (2005)
Ethernet networks are becoming increasingly popular in industrial computercontrolled systems, as they allow for a single network protocol at both the higher and the lower levels of an industrial communication infrastructure. Despite the introduction in the early 90s of a full-duplex operating mode, numerous industrial Ethernet networks still operate in heterogeneous environments, with Ethernet Switching Hubs interconnecting both independent node stations and industrial Ethernet Repeater Hubs. Among node stations interconnected by a Repeater Hub, the network still operates in the traditional shared Ethernet mode; that is, collisions are solved by means of a probabilistic contention resolution algorithm i.e., the medium access is inherently non-deterministic. In this paper, it is analyzed an enhanced collision resolution algorithm for shared Ethernet networks, referred as high priority Binary Exponential Backoff (h-BEB). Such algorithm allows the coexistence of Ethernet standard devices together with modified (real-time) devices in the same network segment. Both the analytical and the simulation timing analysis show that the h-BEB algorithm guarantees a maximum access delay that is significantly smaller than for the case of standard Ethernet stations. Such enhanced collision resolution algorithm enables the traffic separation between standard and modified (real-time) stations, and is therefore able to guarantee a real-time communication behavior in unconstrained traffic environments.